2015
DOI: 10.1002/dvg.22906
|View full text |Cite
|
Sign up to set email alerts
|

The plant homeodomain finger protein MESR4 is essential for embryonic development in Drosophila

Abstract: Misexpression Suppressor of Ras 4 (MESR4), a plant homeodomain (PHD) finger protein with nine zinc-finger motifs has been implicated in various biological processes including the regulation of fat storage and innate immunity in Drosophila. However, the role of MESR4 in the context of development remains unclear. Here it is shown that MESR4 is a nuclear protein essential for embryonic development. Immunostaining of polytene chromosomes using anti-MESR4 antibody revealed that MESR4 binds to numerous bands along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…However, we found that the PHD finger is dispensable for the MESR4 function in germ cell differentiation. Consistent with our observation, previous studies failed to detect the direct association of MESR4 with the modified histones [49]. While we cannot completely exclude that MESR4 is involved in chromatin remodeling, we prefer an alternative hypothesis for the MESR4 function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we found that the PHD finger is dispensable for the MESR4 function in germ cell differentiation. Consistent with our observation, previous studies failed to detect the direct association of MESR4 with the modified histones [49]. While we cannot completely exclude that MESR4 is involved in chromatin remodeling, we prefer an alternative hypothesis for the MESR4 function.…”
Section: Discussionsupporting
confidence: 91%
“…It is able to suppress the constitutively activated Ras-MAPK pathway [47] or the FGF-signaling [48]. In addition, MESR4 is required for the proper control of EGFR/ERK signaling during embryonic development and wing formation [49]. In the adult female GSC niche, the EGFR/ERK pathway is active in the escort cells, and limits the Dpp gradient to the anterior tip of the niche where the GSCs reside [50].…”
Section: Discussionmentioning
confidence: 99%
“…The PHD finger was first identified in Arabidopsis thaliana transcription factor HAT3.1 (a homeodomain-containing protein) and its maize homolog Zmhox1a in 1993 [22]. Since then, many other PHD-finger proteins have been identified in various eukaryotes, including the yeast [23, 24], Drosophila [25, 26] and human [12, 27, 28]. The PHD finger can be defined as a Cys-rich domain of approximately 50~80 amino acids with spatially conserved 8 metal ligands arranged as unique Cys4-His-Cys3 pattern in 4 pairs which can chelate two Zn 2+ atoms and form a cross-brace structure [13, 29, 30].…”
Section: Introductionmentioning
confidence: 99%